Synthesis of Alkene and Ethanol in CO2 Hydrogenation on a Highly Active Sputtering CuNaFe Catalyst - Si, Zhiyan; Wang, Linkai; Han, Yu; Yu, Jiafeng; Ge, Qingjie; Zeng, Chunyang; Sun, Jian (ACS sustainable chemistry & engineering, 2022)
Catalytic hydrogenation of carbon dioxide into chemicals and fuels has moved into the spotlight in the recent carbon-neutral age. However, this sustainable process is still a low efficiency one due to the limitations of the catalyst materials. Herein, we designed a highly active CuNaFe catalyst with a self-made physical sputtering method for CO2 hydrogenation. The total space time yield (STY) rate of high-value olefin and ethanol can reach as high as 833 mg·g–1·h–1 under a mild condition of 310 °C and 3 MPa, which ranks as one of the top performances among related studies. The characterizations demonstrate that the surface of highly dispersed Cu nanoparticles coupled with surrounding Na modified Fe5C2 creates a well-matched process of C–O activation, C–C coupling, and C–O insertion. These findings provide a new and general strategy to fabricate a high-efficiency catalyst for direct CO2 hydrogenation into useful chemicals.